ECONOMIC PERFORMANCE OF THE FIRMS IN AGRICULTURE IN THE AREA OF POSAVINA – "Micro" indicators of competitiveness - Pucar, Stevo (Economics of Agriculture, 2009)
This research deals with the two important topics: the definition of simple ways to determine the competitiveness of agricultural production and use of these indicators to determine the competitiveness of agricultural production in the region of Posavina in BiH. The focus was on the "micro" indicators: revenue per worker, profit per worker and the rate of profit. In this study we focused on the area of Posavina in BiH, as an area of intensive agricultural production. In this area the agricultural production is represented as a significant economic activity and has significant development potential. The selected indicators showed that most types of agricultural production had a relatively good results, which says that agricultural production can be profitable. Therefore, it is of great importance to make the shift from traditional agricultural production based on the production of crops, to more acumulative and profitable activities. The aproach should be to support the gradual redirection of activities, resources, labor force, from less competitive, to more competitive activities.